Survival and prognostic factors from a multicentre large cohort of unselected Italian systemic sclerosis patients. (8th September 2022) - Cacciapaglia, Fabio; Airò, Paolo; Fornaro, Marco; Trerotoli, Paolo; De Lorenzis, Enrico; Corrado, Addolorata; Lazzaroni, Maria Grazia; Natalello, Gerlando; Montini, Fabio; Altomare, Alberto; Urso, Livio; Verardi, Lucrezia; et al.
Abstract: Objectives: Survival and death prognostic factors of SSc patients varied during the past decades. We aimed to update the 5- and 10-year survival rates and identify prognostic factors in a multicentre cohort of Italian SSc patients diagnosed after 2009. Material and methods: Patients who received a diagnosis of SSc after 1 January 2009 and were longitudinally followed up in four Italian rheumatologic centres were retrospectively assessed up to 31 December 2020. Overall survival of SSc patients was described using the Kaplan–Meier method. Predictors of mortality at 10-year follow-up were assessed by the Cox regression model. A comparison of our cohort with the Italian general population was performed by determining the standardized mortality ratio (SMR). Results: A total of 912 patients (91.6% females, 20% dcSSc) were included. Overall survival rates at 5 and 10 years were 94.4% and 89.4%, respectively. The SMR was 0.96 (95% CI 0.81, 1.13), like that expected in the Italian general population. Pulmonary arterial hypertension (PAH) and interstitial lung disease (ILD) associated with pulmonary hypertension (PH) significantly reduced survival ( P  < 0.0001). Main death predictors were male gender (HR = 2.76), diffuse cutaneous involvement (HR = 3.14), older age at diagnosis (HR = 1.08), PAH (HR = 3.21), ILD-associated PH (HR = 4.11), comorbidities (HR = 3.53) and glucocorticoid treatment (HR= 2.02). Conclusions: In the past decade, SSc patients have reached similar mortality of that expected in the Italian general population. Male gender, diffuse cutaneous involvement, comorbidities and PAH with or without ILD represent the main poor prognostic factors.